Higher Order Ocular Aberrations and Their Relation to Refractive Error and Ocular Biometry in Children - Little, Julie-Anne; McCullough, Sara J.; Breslin, Karen M. M.; Saunders, Kathryn J. (Investigative ophthalmology & visual science, 2014)
The interaction between higher order ocular aberrations (HOA) and refractive error is not yet fully understood. This study investigated HOA in relation to refractive error and ocular biometric parameters in a population with a high prevalence of ametropia. The HOA were investigated in two cohorts of Caucasian children aged 9 to 10 and 15 to 16 years (n = 313). These aberrations were measured for a 5-mm pupil with the IRX3 aberrometer. Cycloplegic refractive error and ocular biometry measures, including axial length and corneal curvature, also were assessed with the Shin-Nippon SRW-5000 auto-refractor and Zeiss IOLMaster, respectively. Participants were divided into refractive groups for analysis of HOA. The magnitude of total HOA was higher in this population at 0.27 μm (interquartile range [IQR], 0.22-0.32 μm) than other HOA reported in the literature. The profile of HOA was not significantly different across the two age cohorts or across refractive groups, nor did spherical aberration differ significantly with age (Z₄⁰ = 0.07 μm for both cohorts). Multivariate linear regression analysis demonstrated spherical aberration was significantly related to axial length (but not refractive grouping), with longer eyes having less positive values of fourth order and root mean square (RMS) spherical aberration. This study found no significant difference in HOA across refractive groups. The current study also highlights the importance of knowledge of axial length when analyzing HOA.